2018
DOI: 10.1371/journal.pone.0203563
|View full text |Cite
|
Sign up to set email alerts
|

Silk genes and silk gene expression in the spider Tengella perfuga (Zoropsidae), including a potential cribellar spidroin (CrSp)

Abstract: Most spiders spin multiple types of silk, including silks for reproduction, prey capture, and draglines. Spiders are a megadiverse group and the majority of spider silks remain uncharacterized. For example, nothing is known about the silk molecules of Tengella perfuga, a spider that spins sheet webs lined with cribellar silk. Cribellar silk is a type of adhesive capture thread composed of numerous fibrils that originate from a specialized plate-like spinning organ called the cribellum. The predominant componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 68 publications
4
25
0
Order By: Relevance
“…1 b,c). However, as mentioned in a previous study 43 , other than that, only features commonly found in spacers were observed (TT or SS), and no other noteworthy motif was found. On the other hand, Pflag had similar motifs as Flag, although the motif lengths of Pflag and Flag were different.…”
Section: Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…1 b,c). However, as mentioned in a previous study 43 , other than that, only features commonly found in spacers were observed (TT or SS), and no other noteworthy motif was found. On the other hand, Pflag had similar motifs as Flag, although the motif lengths of Pflag and Flag were different.…”
Section: Resultssupporting
confidence: 54%
“…The cribellate spider-associated genes ( CrSp and Pflag ) were also searched based on the partial CrSp candidate sequence in T. perfuga 43 and the Flag sequence in Araneus ventricosus 48 . As a result, a full picture of the genes, including the repetitive and N/C-terminal domains of CrSp and Pflag , was obtained (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations